2003
DOI: 10.1007/s00011-003-1189-1
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of diclofenac-induced anti-inflammatory response by aminoguanidine in carrageenan-induced acute inflammation in rats: The role of nitric oxide

Abstract: These results show that AG markedly potentiates the anti-inflammatory activity of diclofenac at 6 h and this potentiation effect is nitric oxide-dependent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 41 publications
(43 reference statements)
2
19
0
1
Order By: Relevance
“…Marked increases of ear weights (Al-Majed et al, 2003;Ojewole 2005), and severe vasodilation and edematous changes of ear skin at histopathological observation (De La Puerta et al, 1996;Kou et al, 2003;Rotelli et al, 2003;Kim et al, 2007) were detected as signs of acute inflammation after topical application of xylene in the present study. However, ear weight increases and histopathological changes were dose-dependently decreased after pretreatment with three different dosages of PR extracts in the present study.…”
Section: Discussionsupporting
confidence: 62%
“…Marked increases of ear weights (Al-Majed et al, 2003;Ojewole 2005), and severe vasodilation and edematous changes of ear skin at histopathological observation (De La Puerta et al, 1996;Kou et al, 2003;Rotelli et al, 2003;Kim et al, 2007) were detected as signs of acute inflammation after topical application of xylene in the present study. However, ear weight increases and histopathological changes were dose-dependently decreased after pretreatment with three different dosages of PR extracts in the present study.…”
Section: Discussionsupporting
confidence: 62%
“…After topical application of xylene, marked increases in ear weight were detected as a result of the acute inflammation response; these increases in ear weight have been used as valuable markers for anti-inflammatory effects 21,22) . In the present study, the increases in ear weight were dosedependently inhibited by MIL treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests the idea that the increase in the rate of expression lags the increase in enzyme activity. Further expression of iNOS requires an additional synthesis which is time-dependent (56,57). Furthermore, the increase in total NOS activity was prevented by 1400W, indicating that increased iNOS expression and activity could likely cause NO overproduction in response to ischemia and reperfusion (Fig.16).…”
Section: Role Of Inos and Rns In Platelet-arteriolar Wall Interactionmentioning
confidence: 93%
“…However, it has been shown that NO can be both protective (61)(62)(63) and deleterious to vascular homeostasis (64) through direct effects on cell signaling, as well as indirect actions. Overproduction of NO via the inducible nitric oxide synthase (iNOS) pathway is an important component in the pathogenesis of IR injury (55)(56)(57)72). During IR, excess NO production has been attributed to iNOS that is not stimulated under normal conditions, but can be induced within 2 h of lung reperfusion (65) and results in upregulation of adhesion molecules (68).…”
Section: Role Of Nitric Oxide In Pulmonary Irmentioning
confidence: 99%
See 1 more Smart Citation